The dynamics of global sourcing. perspectives and practices 6th Global sourcing workshop 2012, Courchevel, France, March 12-15, 2012, Revised Selected Papers - Oshri, Ilan; Willcocks, Leslie P.; Kotlarsky, Julia (Lecture Notes in Business Information Processing, 2012)
This book contains 13 carefully revised and selected papers from the 6th Workshop on Global Sourcing, held in Courchevel, France, during March 12-15, 2012. They have been selected from 46 submissions and represent both client and supplier perspectives on sourcing of global services. This volume is intended for use by students, academics, and practitioners interested in the outsourcing and offshoring of information technology and business processes. It offers a review of the key topics in outsourcing and offshoring, populated with practical frameworks that serve as a toolkit for students and managers. The topics discussed combine theoretical and practical insights, and they are extensively illustrated by case studies from client and vendor organizations. Last but not least, the book examines current and future trends in outsourcing and offshoring, paying particular attention to the centrality of innovation in sourcing arrangements, and how innovation can be realized in outsourcing.